2021
DOI: 10.1172/jci.insight.145228
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Immunization with Peptide-based Immunogenic Complex Enhances BCG Vaccine Efficacy in murine model of Tuberculosis

Abstract: Prime-boost immunization strategies are required to control the global tuberculosis (TB) pandemic, which claims approximately 3 lives every minute. Here, we have generated an immunogenic complex against Mycobacterium tuberculosis ( M.tb ), consisting of promiscuous T cell epitopes ( M.tb peptides) and TLR ligands assembled in liposomes. Interestingly, this complex (peptide–TLR agonist–liposomes; PTL) induced significant activation of CD4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Previous studies on TB subunit vaccines have provided a large number of vaccine candidate antigens for peptide-based vaccines development, such as Ag85A (Rv3804c) ( 241 ), Ag85B (Rv1886c) ( 116 , 202 , 239 , 240 ), 6-kDa early secretory antigenic target (ESAT-6, Rv3875) ( 222 , 223 , 238 , 239 ), heat shock protein HspX (also known as Hsp16.3, Acr, and 14 kDa antigen, Rv2031c) ( 115 , 146 , 202 , 210 , 211 , 242 ), TB10.4 (Rv0288) ( 2 , 115 , 211 , 240 ), Rv0476 ( 211 ), Hsp65 ( 202 ), 19-kDa lipoprotein (Rv3763) ( 202 ), Rv1733c ( 202 , 203 ), PE/PPE proteins ( 2 , 243 , 244 , 248 ), MPT64 (Rv1980c) ( 246 , 247 ), Mtb8.4 ( 2 ), and resuscitation-promoting factors (Rpfs) ( 2 , 228 ). These antigens have been reported to be attractive vaccine candidates for preventing and controlling TB.…”
Section: Research Status Of Tb Peptide-based Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on TB subunit vaccines have provided a large number of vaccine candidate antigens for peptide-based vaccines development, such as Ag85A (Rv3804c) ( 241 ), Ag85B (Rv1886c) ( 116 , 202 , 239 , 240 ), 6-kDa early secretory antigenic target (ESAT-6, Rv3875) ( 222 , 223 , 238 , 239 ), heat shock protein HspX (also known as Hsp16.3, Acr, and 14 kDa antigen, Rv2031c) ( 115 , 146 , 202 , 210 , 211 , 242 ), TB10.4 (Rv0288) ( 2 , 115 , 211 , 240 ), Rv0476 ( 211 ), Hsp65 ( 202 ), 19-kDa lipoprotein (Rv3763) ( 202 ), Rv1733c ( 202 , 203 ), PE/PPE proteins ( 2 , 243 , 244 , 248 ), MPT64 (Rv1980c) ( 246 , 247 ), Mtb8.4 ( 2 ), and resuscitation-promoting factors (Rpfs) ( 2 , 228 ). These antigens have been reported to be attractive vaccine candidates for preventing and controlling TB.…”
Section: Research Status Of Tb Peptide-based Vaccinesmentioning
confidence: 99%
“…Previous studies have shown that Ag85A and Ag85B proteins are rich in epitope resources, giving them a distinct advantage in constructing peptide-based vaccines (257,265). Kumar S et al generated a vaccine mixture (peptide-TLR agonist-liposomes, abbreviation for PTL), consisting of three Ag85B peptides, four ESAT-6 peptides, TLR2 agonist Pam3Cys-SK-4, and TLR9 agonist CpG ODN (Table 3) (239). Interestingly, the BCG-PTL coimmunization enhanced the proportion of vaccineinduced Tcm cells and polyfunctional cytokine responses and increased the defensive efficiency against TB compared with BCG vaccination (239).…”
Section: Peptide-basedmentioning
confidence: 99%
“…It is well-known that only available vaccine against TB is BCG that fails to induce long term memory and thereby insufficient to prevent resuscitation ( Negi et al., 2022 ). Therefore, a potential adjunct complex, termed as peptide-TLR agonist-liposome (PTL) when administered with BCG enhances the long-term memory and reduces the rate of reactivation, thereby reduction in bacterial burden in the lungs of mice ( Kumar et al., 2021 ).…”
Section: Resuscitation Of Dormant Mtbmentioning
confidence: 99%
“…Nasal and pulmonary routes aim to enhance the induction of secretary IgA antibody in nasal passages and lung mucosal sites [59] . Indeed, nasal and pulmonary routes were shown to be effective to provide immune responses against influenza [60] , [61] and tuberculosis [62] , [63] , respectively. Subcutaneous route can allow the migration of vaccine antigens to lymph nodes, the primary organs of adaptive immune response [64] .…”
Section: Vaccine Delivery Systemsmentioning
confidence: 99%